«Уметник од Русиjа»: македонские страницы жизни и творчества художника-эмигранта ивана Мельникова - Lapaeva, Nataliya B. (Philological Studies, 2019)
The article considers the “macedonian” period of creativity Russian artist-emigrant Ivan Melnikov. Analyzed the destinations of activities Melnikov: as the creator of icons and frescoes in the Macedonian and Serbian monasteries and churches, as the theater artist and scenographer, as the teacher of iconography. Creativity of Melnikov considered in the context of the fate of the Russian emigration in the Kingdom of Serbs, Croats, Slovenes and on the background of the life and activities of the Russian colony in the Macedonian town Bitola. It is alleged that Melnikov, like many members of the Russian emigration 1920-30, kept his national identity and strove to cultural dialogue with the Slavic peoples among whom he lived.